School Sports Club in South Korea: Supporting Middle School Students' Physical Activity Engagement and Social-Emotional Development in Schools. Issue 4 (4th May 2023) - Cho, Kyuil; Tsuda, Emi; Oh, Daekyun
Abstract: Adolescents in South Korea have been facing physical (physical inactivity) and social-emotional (e.g., bullying and suicide) challenges in the last few decades. To address these issues, the Ministry of Education in South Korea implemented School Sports Club as a part of the school curriculum. This article introduces the overview, the goals and structure, the status quo, and the future directions of the School Sports Club. School Sports Club is offered during the regular school time and a required curriculum. The primary goal of the School Sports Club is to increase physical activity opportunities, strengthen humanistic education, prevent bullying, and ultimately develop a positive attitude in their school life among students. In School Sports Club, teachers are allowed to select the content that would best meet their students' needs and school contexts. While there are some challenges, the students have positive experiences in School Sports Club. In summary, School Sports Club is one way to support students' physical activity engagement and social-emotional learning in school settings.